2009
DOI: 10.1007/s00167-009-0767-3
|View full text |Cite
|
Sign up to set email alerts
|

Back pain and MRI changes in the thoraco-lumbar spine of top athletes in four different sports: a 15-year follow-up study

Abstract: A total 71 male athletes (weight lifters, wrestlers, orienteers, and ice-hockey players) and 21 non-athletes were randomly selected, for a baseline MRI study. After 15 years all the participants at baseline were invited to take part in a follow-up examination, including a questionnaire on back pain and a follow-up MRI examination. Thirty-two athletes and all non-athletes had disc height reduction at one or several disc levels. Disc degeneration was found in more than 90% of the athletes and deterioration had o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
141
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(152 citation statements)
references
References 28 publications
11
141
0
Order By: Relevance
“…The prevalence of back pain is much higher among active athletes participating in sports with heavy loads on the spine than among other athletes and nonathletes, and it has been reported in between 10 % and 91 % of athletes (Jackson 1979;Sward et al 1990b;Harvey and Tanner 1991;Eriksson et al 1996;Kujala et al 1996a;Sassmannshausen and Smith 2002;Bahr et al 2004;Baranto et al 2006Baranto et al , 2009b. Back pain among athletes may result from acute macrotrauma, repetitive microtrauma (stress), or a combination of these two mechanisms (Kujala et al 1996b).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The prevalence of back pain is much higher among active athletes participating in sports with heavy loads on the spine than among other athletes and nonathletes, and it has been reported in between 10 % and 91 % of athletes (Jackson 1979;Sward et al 1990b;Harvey and Tanner 1991;Eriksson et al 1996;Kujala et al 1996a;Sassmannshausen and Smith 2002;Bahr et al 2004;Baranto et al 2006Baranto et al , 2009b. Back pain among athletes may result from acute macrotrauma, repetitive microtrauma (stress), or a combination of these two mechanisms (Kujala et al 1996b).…”
Section: Introductionmentioning
confidence: 93%
“…However, as back pain is also a common symptom in the general population, it has been difficult firmly to establish, in the literature, the relationship between plain radiography or MRI findings and back pain. However, in recent studies, these anatomic abnormalities have been reported to be correlated with the symptoms (Sward et al 1991;Kujala et al 1996a; Baranto et al 2006Baranto et al , 2009b.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Intensive exercises causing spinal strain from the earliest years may increase the risk of developing musculoskeletal disorders and affect the process of growth [5,6]. Moreover, participation in sports activities is related to the risk of injuries.…”
Section: Introductionmentioning
confidence: 99%